Nequaquam tantum belli: News and Politics in Livy, Book 35.1-8 - Clark, Jessica H. (Histos, 2014)
In the opening chapters of Book 35, Livy raises the possibility of a serious revolt in Spain in 194 BCE, a possibility he proceeds to complicate and, ultimately, to reject. Interwoven with these chapters is a complementary narrative of events in Cisalpine Gaul. While both sequences apprise the reader of Roman magistrates’ activities abroad, this is not their primary role. Rather, the opening of Book 35 serves as an object lesson on the process of politics at Rome, as the Senate and individuals within its ranks experience (and exploit) the difficulties of managing conflicts in increasingly distant provinces.